2020
DOI: 10.1590/pboci.2020.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermocycling on the Colour Stability of Aesthetic Restorative Materials: An in-vitro Spectrophotometric Analysis

Abstract: To compare the color stability of Cention N, Fuji IX GP Extra, and Fuji IX GP after thermocycling. Material and Methods: Ten discs of each material of dimension 10 x 1 mm were prepared using a split mold. The preparations of the specimens were done according to the powder/liquid ratio as recommended by the manufacturers [4.6:1, 3.4:1 and 3.6:1 for the groups I, II, and III, respectively]. After setting, the samples were retrieved, and the thickness of each specimen was measured using a micrometer at five diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…In our study, no statistically significant difference was observed when the surface roughness values (Ra) of the Cention-N composite were compared with the other composite groups (p>0.05). In the study of Bhattacharya et al investigating the effect of thermal cycle on color stability in various composites, it was stated that Cention-N composite showed better color stability compared to Fuji IX GP and Fuji IX GP Extra (16). Our study determined that Cention-N samples polymerized with light have the lowest ΔE00 values in all solution types.…”
Section: Discussionsupporting
confidence: 48%
“…In our study, no statistically significant difference was observed when the surface roughness values (Ra) of the Cention-N composite were compared with the other composite groups (p>0.05). In the study of Bhattacharya et al investigating the effect of thermal cycle on color stability in various composites, it was stated that Cention-N composite showed better color stability compared to Fuji IX GP and Fuji IX GP Extra (16). Our study determined that Cention-N samples polymerized with light have the lowest ΔE00 values in all solution types.…”
Section: Discussionsupporting
confidence: 48%
“…The materials were separated into three categories. From the result he concluded that Cention N had superior color stability when compared to glass ionomer cement material [23]. Similarly, our study had better color stability in thermocycled cention N samples.…”
Section: Resultssupporting
confidence: 68%
“…In this study Cention-N presented high antibacterial activity as it in acidic PH. due to presence of bacteria, released higher amounts of fluoride ion, the probable description is that Cention-N may responded more forcefully in the existence of acidic situation where possibly the surface unaffected layer may washed-out quicker, so baring the matrix for improved liberation of fluoride ions (5) . Moreover, Cention-N revealed elevated alkalizing ability in acidic pH.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Cention-N revealed elevated alkalizing ability in acidic pH. This could be owing to the hydroxyl and calcium ions liberate by alkaline glass fillers from Cention-N, that are capable to have exact influence on the pH levels, thus producing environments where the additional acidity owing to cariogenic bacterial activity could be counteracted (5) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation